Sustainability Analysis of Batik MSMEs from the Marketing, Regeneration, and Environmental Dimensions: A Multiple Case Study of Three MSMEs in Laweyan Batik Village - Hidayatun Nisa; Tri Murwaningsih (Journal of Business, Management, and Social Studies, 2026)
This study aims to analyze Batik MSMEs in Laweyan Batik Village from the dimensions of marketing, regeneration, and environment through multiple case studies of three MSMEs representing micro, small, and medium enterprises. This study uses a qualitative approach with a multiple case study design involving three Batik MSMEs as case units, namely Batik Tjap Tiga Negeri (micro-scale), Batik Putra Laweyan (small-scale), and Batik Putra Mahkota  (medium-scale). Data were collected through semi-structured interviews, observation, and documentation, with data validity tested through triangulation of source and techniques and analyzed using interactive analysis techniques both in each case and across cases. The three cases show very different termination profiles. Batik Tjap Tiga Negeri shows weak sustainability in the third dimension, with conventional marketing, no succession mechanism, and very minimal wastewater treatment. Batik Putra Laweyan shows a transitional sustainability profile, namely starting to utilize social media for marketing, informally involving the second generation, and joining a communal wastewater treatment plant (IPAL). Batik Mahkota Laweyan demonstrates strong sustainability, with an integrated marketing strategy, structured cross-generational cadre development, and a certified independent waste management system.